Ventilatory responses and breathing comfort depending on the use of facemask during paddling - López-Plaza, D.; Abellán-Aynés, O.; Isorna, M.; Alacid, F.; Manonelles, P. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
Introduction The virus SARS-CoV-2 has normalized the use of facemask to prevent its contagion and transmission since a common way of spreading is by close contact through respiratory droplets. As a result, many sport activities in several countries are still performed wearing facemask. Previous studies have analyzed their influence on physiological parameters but not conclusive results were obtained. Apparently, most of the inconveniences derived from the use of facemask might come from mental stress and discomfort rather than cardiorespiratory limitations. Therefore, the aim of this research was to determine whether wearing a facemask influenced ventilatory and breathing comfort parameters during a maximum incremental kayak-ergometer test in active paddlers.